The treatment of intervertebral disc degeneration using Traditional Chinese Medicine. (5th December 2020) - zhu, Liguo; Yu, Changsui; Zhang, Xiaofeng; Yu, Zhongbao; Zhan, Fengyuan; Yu, Xin; Wang, Shuren; He, Feng; Han, Yusheng; Zhao, He
Abstract: Ethnopharmacological relevance: Intervertebral disc degeneration (IDD) is one of the most common causes of chronic low back pain that spending a lot of workforces and financial resources, seriously affecting human physical and mental health. Clinically used drug treatments and surgical treatments cannot fundamentally relieve the disease and have a risk of recurrence. Traditional Chinese Medicine (TCM) has a history of more than a thousand years in the prevention and treatment of IDD. However, so far, there are few reviews on the treatment of IDD by TCM. Therefore, it is crucial and necessary to systematically mine the existing literature on the treatment of IDD with TCM. This paper strives to systematically describe the modern medicine and TCM theoretical research on IDD, progress in the treatment of IDD and focuses on the treatment of IDD by TCM, which would lay some theoretical foundation and provide new directions for future research. Materials and methods: Information on clinical observations, animal experiments and relevant pharmacology data about the treatment of IDD were gathered from various sources including traditional Chinese books and Chinese Pharmacopoeia, scientific databases (Elsevier, PubMed, Science Direct, Baidu Scholar, CNKI, Spring Link, Web of Science) and from different professional websites. Results: This review mainly introduces the current research on the theoretical research on IDD, the combination principle of the TCM formula, and the underlying mechanism of the formula and active ingredients. Conclusions: At present, domestic and foreign scholars have carried out a lot of research in different ways, such as the molecular mechanism and predisposing factors of IDD, which provides theoretical development and clinical practice significance for future research. TCM, as a multi-component and multi-targeted drug, can produce synergistic effects to exert its efficacy. Therefore, the development of TCM with more specific functions and practical data will not only become a significant trend in the world market but also has an irreplaceable role in the future treatment of IDD. Graphical abstract: The molecular biological behavior of IDD and the action mechanism of representative TCM formulas and its compounds. Image 1